PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2019-2021) - Rianthy, Gina Anggi; HS, Sri Wahyuni (Patria Artha Journal of Accounting dan Financial Reporting, 2024)
This study is aimed to determine the effect of good corporate governance on financial performance listed on Indonesia Stock Exchange. The type of research used explanatory research with a quantitative approach. This study used secondary data obtained from the annual reports of banking.companies listed on Indonesia Stock Exchange (IDX). The population in this study were banking companies listed on Indonesia Stock Exchange, with sample selected using purposive sampling method as many as banking companies. The data were analyzed using multiple regression analysis techniques with the help of the SPSS program. The results showed (1) the audit committee had no significant effect performance; (2) Independent commissioners had no significant effect on financial performance; (3) The independent board of commissioners had no significant effect on financial performance; (4) The board of directors had a significant effect on financial performance; (5) The board commissioners had no effect on financial performance.